2007
DOI: 10.2144/000112390
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis by Retroviral Insertion in Chemical Mutagen-Generated Quasi-Haploid Mammalian Cells

Abstract: Diploidy is a major obstacle to the mutagenic analysis of function in cultured mammalian cells. Here, we show that 6-8 rounds of chemical mutagenesis generates quasi-haploid cells that can be used as targets for insertional mutagenesis using a specially designed retroviral vector that permits rapid identification of disrupted genes in each cell that bears a phenotype of interest. The utility of combined chemical and insertional mutagenesis is illustrated by the identification of novel host genes that are requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 45 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Recent studies have shown that TNF-␣ surface delivery and secretion is regulated through a process involving cholesterol-dependent lipid raft formation at the phagocytic cup of activated macrophages (7,12); however, it is unknown how TNF-␣ surface delivery is regulated and whether it can be facilitated upon TLR activation. We used a functional gene identification procedure using retrovirus integration-generated mutagenesis (13)(14)(15) and identified that cathepsin B activity was required for optimal TNF-␣ transportation to the plasma membrane. Cathepsin B is a lysosomal cysteine protease involved in the degradation of cellular proteins in lysosomes.…”
mentioning
confidence: 99%
“…Recent studies have shown that TNF-␣ surface delivery and secretion is regulated through a process involving cholesterol-dependent lipid raft formation at the phagocytic cup of activated macrophages (7,12); however, it is unknown how TNF-␣ surface delivery is regulated and whether it can be facilitated upon TLR activation. We used a functional gene identification procedure using retrovirus integration-generated mutagenesis (13)(14)(15) and identified that cathepsin B activity was required for optimal TNF-␣ transportation to the plasma membrane. Cathepsin B is a lysosomal cysteine protease involved in the degradation of cellular proteins in lysosomes.…”
mentioning
confidence: 99%
“…As previously reported, a combination of chemical and insertional mutagenesis can be used for the mutagenic screen in cultured mammalian cells (Kim et al, 2007). We generated a pool of theoretically quasi-haploid RAW 264.7 cells, which have 99.5% of all genes in random mutation after eight rounds of N-ethyl-N-nitrosourea (ENU) treatment (Kim et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…We generated a pool of theoretically quasi-haploid RAW 264.7 cells, which have 99.5% of all genes in random mutation after eight rounds of N-ethyl-N-nitrosourea (ENU) treatment (Kim et al, 2007). Then, the retroviral insertion was introduced into the quasi-haploid cell pool to abolish gene expression or produce a truncated gene product.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations